Rapid Genotyping of Human Papillomavirus by Desorption Electrospray Ionization Mass Spectrometry. (5th May 2017) - Kim, Shin Hye; Hong, Sun Pyo; Cho, Woojae; Kim, Jeongkwon; Lee, Tae Geol; Yoon, Sohee
Abstract : This study describes a new approach to rapidly detecting of human papillomavirus (HPV) DNA using desorption electrospray ionization mass spectrometry (DESI‐MS) without sample preparation such as extraction or purification. Our strategy utilizes the ambient ionization mass spectrometry for ionizing and detecting oligonucleotides from restriction fragment mass polymorphism (RFMP) assay, and is to identify which HPV genotype from combinations of multiply charged ions of oligonucleotides. In DESI‐MS, the spray solvent system operates at the stage of washing a complex mixture of polymerase chain reaction (PCR) products, so that the oligonucleotides can be detected without sample treatment. The study was verified to rapid diagnosis of cervical cancer by detecting and genotyping of HPV DNA based RFMP assay using DESI‐MS. Abstract :